A functional application of the spacing effect to improve learning and memory in persons with multiple sclerosis - Goverover, Yael; Hillary, Frank G.; Chiaravalloti, Nancy; Arango-Lasprilla, Juan Carlos; DeLuca, John (Journal of clinical and experimental neuropsychology, 2009)
The present study examined the utility of using spaced learning trials (when trials are distributed over time) versus massed learning trials (consecutive learning trials) in the acquisition of everyday functional tasks. In a within-subjects design, 20 participants with multiple sclerosis (MS) and 18 healthy controls (HC) completed two route learning tasks and two paragraph reading tasks. One task in each area was presented in the "spaced" condition, in which the task was presented to the participants three times with 5-minutes break between each trial, and the second task in each area was presented in the "massed" condition, in which the task was presented three consecutive times to the participants. The dependent variables consisted of recall and recognition of the paragraphs and routes both immediately and 30 minutes following initial learning. Results showed that for paragraph learning, the spaced condition significantly enhanced memory performance for this task relative to the massed condition. However, this effect was not demonstrated in the route learning task. Thus, the spacing effect can be beneficial to enhance recall and performance of activities of daily living for individuals with MS; however, this effect was significant for verbal tasks stimuli, but not for visual tasks stimuli. It will be important during future investigations to better characterize the factors that maximize the spacing effect.